Korelasi Antara Self Efficacy Dan Pengetahuan Bahaya Rokok Terhadap Motivasi Untuk Berhenti Merokok Pada Mahasiswa Perokok Berat - Siska Adinda Prabowo Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2021)
This research aims to know the relationship between self-efficacy and the knowledge of the dangers of smoking in motivating chaing smoker students in Semarang to stop smoking. Population criteria is used in this study is chain smoker with average consumption in more than 15 cigarettes / day and still on active status as a student. Data analysis technique which is used multiple regression analysis. The results of the research indicates that (1) there is a significant relationship between self-efficacy and knowledge of the dangers of smoking to stop smoking motivation of chain smoker with R = 0.855; F = 40.737 (p <0.01) (2) there is a significant positive relationship between self-efficacy and motivation to stop smoking which , (3) there is a significant positive correlation between knowledge of hazards with the motivation to stop smoking cigarettes where the value